Generalized analysis of the multi-well interference test in hydrocarbon reservoirs (2003)
This study presents a generalized analytical formulation of the Multi-Well Interference test problem using the concept of the source arid sink functions as a tool for solving the basic interference equations. The much broader case, featuring inner well boundary conditions with skin and storage factors at both the active and the several observation wells, is considered. The general nature of the formulation allows for the analyses of non-homogeneous reservoirs and hence the concepts of reservoir directional permeability and the related issues of reservoir principal axes of permeability were addressed. Most of the published cases of interference tests were identified as limiting cases of the generalized formulation.